Straight from the Heartland: New Sincerity and the American Midwest - Daalder, J (2016)
As more and more critics now write about postmodernism in the past tense, the “New Sincerity” of a group of late twentieth-century American writers, led by David Foster Wallace, Jonathan Franzen, and Richard Powers, has been championed as one of its successors. In response to these increasingly widespread views, this dissertation argues that much more can be learned about these three writers when we stop thinking of their work within this “end of postmodernism” discourse. Instead of attempting to make claims about its novelty, this thesis conducts a literary-historical inquiry into the New Sincerity, arguing that its roots extend across postmodernism and reach back to regionalism, in particular from the midwestern provinces that all three authors grew up in and that occupy a central place in their work. Though regionalism’s subject matter, small-town America, is commonly believed to have died in the postwar period, it is this “death of the prairie town” and its symbolic afterlife that have opened up new literary possibilities outside the realm of conventional regionalism. The powerful feelings of loss and nostalgia that its death has engendered are precisely those of which Wallace, Franzen, Powers, and the New Sincerity in general make creative use. The thesis examines how they do so in a series of three extended chapters, each of which focuses on one author. The first chapter pays careful attention to Wallace’s re-imagining of the Midwest over the course of his career and reveals how he constantly deviated from the literary trajectory he had outlined in his essay “E Unibus Pluram,” a key text in the “end of postmodernism” discourse. The second chapter explores what role the Midwest plays in Franzen’s authorial self-presentation and his contradictory attempts to balance “high-art” status with an anti-elitist image. The third and final chapter gets to the root of Powers’s problems with flat characters by examining how he all too readily relies on the Midwest and its stereotypical associations with all-American goodness in his attempts to create endearing characters. Here, as well as in the other two chapters, it is the construction of a symbolic “heartland” that plays a central role in the creative process behind the author’s New Sincerity writing.